An evaluation of the impact of environmental regulation on the efficiency of technology innovation using the combined DEA model: A case study of Xi'an, China. (October 2018) - Li, Hui; Zhang, Jingxiao; Wang, Chao; Wang, Yujie; Coffey, Vaughan
Highlights: Exploring the impact of environmental regulation on the efficiency of technological innovation in an innovative city. Proposing a model to analyze the efficiency's spatial-temporal evolution further. Using the panel data of Xi'an from China to analyze the technical efficiency with the 3-stage and Network DEA model. Environmental regulation has no significant influence on the technological innovation efficiency of Xi'an. Xi'an has four kinds of technological innovation mode, and differences exist between the different innovation system and its subsystems. Abstract: The objective of this paper is to explore the impact of environmental regulation on the efficiency of technological innovation and its temporal and spatial evolution in an innovative city with a combined Data Envelopment Analysis (DEA) model. DEA is a common non-parametric frontier model for studying multi-input and multi-output systems. The DEA method uses an input-output index data to mine information such as technology frontier and efficiency evaluation relative to reference technology. Using environmental factors, the efficiency of technological innovation in Xi'an from 2006 to 2015 is measured. The research results show that low scale efficiency is the main factor that restricts the efficiency of technological innovation in innovative city Xi'an. Environmental regulations have no influence on the measurement of technological innovation efficiency in Xi'an. The "Porter hypothesis" is not tenable. There are some differences in the pure technical and scale efficiencies of the two subsystems (R&D and technology transformation) of the network DEA model. The technology transformation process has a more important objective position in the innovation system of Xi'an. The results provide a valuable reference for the measurement of technological innovation efficiency and the formulation and implementation of environmental regulation policies in the innovative cities of developing counties.